A BIBLIOMETRIC ANALYSIS OF CARBON NANOTUBES SYNTHESIS RESEARCH USING VOSVIEWER - Arbiansyah Aldhafi; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2021)
Carbon nanotubes (CNTs) have been rigorously studied during the past decade due to their extraordinary physical, chemical, mechanical, electrical and optical properties. The purpose of this research is to conduct bibliometric analysis in carbon nanotubes synthesis by combining mapping analysis using VOSviewer software. Application reference manager used to obtain research data, namely Mendeley. The data obtained is the result of a search based on the keyword